A spatial and SWOT approach to earthquake mitigation strategy - M. Roja Nabil Hadizar; Aksela Dian Fista; Virna Amelia; M. Fahry Prayoga; Nandi Haerudin; Rahmi Mulyasari; Rahmat Catur; Karyanto (Journal of Environment and Geography Education, 2025)
Background: Bandar Lampung is situated in a seismically active region influenced by the subduction of the Indo-Australian and Eurasian plates, which increases its susceptibility to earthquake hazards. This study aims to evaluate the level of earthquake vulnerability and formulate appropriate mitigation strategies using a spatial and SWOT-based approach. Methods: The methods applied include historical earthquake data analysis, hazard zone mapping, spatial analysis through Geographic Information Systems (GIS), and a review of existing disaster mitigation policies. Findings: The results indicate that during March 2024, 146 earthquake events were recorded, of which 135 were shallow (<60 km) and mainly concentrated in the subduction zone southwest of Lampung. Vulnerability and population density mapping further identified Kedaton, Rajabasa, and Tanjung Karang Pusat as high-risk districts. Conclusion: Based on these findings, recommended mitigation strategies include the enforcement of earthquake-resistant building codes, integration of risk-based considerations into spatial planning, the development of public education and awareness programs, and the strengthening of early warning systems. The study highlights that a spatially informed and policy-oriented approach can effectively reduce the potential impacts of earthquakes and enhance community resilience in Bandar Lampung City. Novelty/Originality of this article: The novelty lies in combining spatial analysis, vulnerability mapping, and a SWOT-based policy framework to produce integrated and location-specific earthquake mitigation strategies for Bandar Lampung City.